"Um nome a zelar" : histórias de uma quilombola do norte do Espírito Santo - Costa, Renata Beatriz Rodrigues da (2018)
This dissertation confers the ways in which women from black cimarron communities develop relations of strength and power in the northern Espírito Santo. Describing the moral careers of the quilombolas and making inroads in their cosmopolitanism allowed to elucidate new strategies in the search for territorial rights. Thus, the biography of a cimarrone and the description of a project of construction of a terreiro of Umbanda conducted by her in a community governed by catholic rites and a family devotion that has trance are the elements of analysis. The ethnography is the result of a field work carried out in the quilombola community of Linharinho, located in the city of Conceição da Barra in the state of Espírito Santo. An analysis is made of how cimarrones build initiatives and how they are received in and out of Linharinho. From this, it is possible to glimpse a more general plan in which the cimarrones construct projects, negotiate spaces, create collectively through groups and associations, means to modify their reality and set their own demands, either by appealing to political structures such as associations of farmers or family memory as an element of distinction. The political action of the female cimarron leaderships takes place in a context of struggle for territory. The results suggest that the dynamics of power among cimarrones are also based on the notion of spirituality as family devotion. In this scenario, Umbandist practices revealed cosmologies that value the preservation of relations with nature, nonhuman beings and that indicate singular and symbolic ways in the maintenance of the right and belonging to the land.